LITERATUR REVIEW: ANALISIS MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT(CMP) DALAM MENINGKATAN KEMAMPUAN METAKOGNI SISWA - hikmah; Aisyah Nursyam (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
Metacognitive ability is an essential component of mathematics learning because it helps students plan, monitor, and evaluate their thinking strategies in problem solving. This study aims to systematically analyze various research findings on the implementation of the Connected Mathematics Project (CMP) learning model in improving students’ metacognitive skills. The research method used is a Systematic Literature Review (SLR) of 30 articles published between 2020 and 2025, obtained from databases such as Google Scholar, DOAJ, Garuda, and Neliti. The analysis was conducted through four stages: searching, selecting, content analysis, and synthesizing the findings. The results show that CMP is effective in enhancing students’ conceptual understanding, mathematical reasoning, communication, and reflective thinking skills. The core components of CMP — problem-centered learning, mathematical connections, and collaborative reflection — are aligned with the metacognitive aspects of planning, monitoring, and evaluating one’s thinking. Most studies indicate that CMP encourages reflective thinking, increases learning awareness, and reduces mathematics anxiety. However, limitations remain in measuring metacognitive indicators, and there is a lack of studies integrating CMP with digital media or validated instruments such as the Metacognitive Awareness Inventory (MAI). Overall, CMP has strong potential to be developed as a metacognitive-based mathematics learning framework that fosters reflective, creative, and adaptive learners suited to the demands of 21st-century education.